The story of Miss Moppet - Potter, Beatrix 1866-1943 (Dodo Press, 2009)
A mouse always seems to get the best of a kitten named Miss Moppet.
Keywords: Cats / Pictorial works / Juvenile fiction; Cats -- Pictorial works -- Juvenile fiction; Children's stories - Pictorial works